Use of dietary fenugreek (Trigonella foenum-graecum L.) seed for the production of safe broiler lean meat (Research in Agriculture Livestock and Fisheries, 2016)
An experiment was conducted for a period of 28 days to determine the dietary effect of fenugreek seeds (FGS) on the productive and economic performances of broilers. A total of 400 day-old Hubbard Classic straight run broiler chicks were randomly allocated to 5 isonitrogenous and iso-caloric dietary treatment groups, each having 80 chicks in 4 replications of 20 numbers, in a completely randomized design (CRD). Broilers were fed ad libitum on either basal diet with (positive control) or without (negative control) 0.1% antibiotic (used as antibiotic growth promoter; AGP) or basal diet containing 1.0%, 2.0% or 3.0% FGS. There were no differences in live weight, feed intake and feed conversion ratio (FCR) among the treatment groups for broilers up to 14 days of age (P>0.05). Broilers fed on the diet containing FGS exhibited significantly better productive performances than those fed on AGP (P